Implementation of Regional Government Policy in Improving Sustainable Tourism Development in Ciamis District - Asep Nurdin Rosihan Anwar; Budiawan, Arie; Endah Vestikowati (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This research aims to assess the extent to which the implementation of local government policies increases sustainable tourism development in the Ciamis Regency. The research method used is qualitative descriptive research. Data collection techniques include field studies (interviews and observations), documentation studies, and library research. The interactive descriptive method is the data analysis methodology employed. Qualitative model which includes data reduction, data presentation and drawing conclusions. Based on research findings and discussions, it appears that the implementation of sustainable tourism development policies in Ciamis Regency has not been optimal. This is explained by the dimensions and indicators of policy implementation: communication, resources, disposition, and bureaucratic structure. It was also explained that the dimensions and indicators of sustainable tourism development in Ciamis Regency have not been implemented optimally, as seen from factors such as participation, stakeholder involvement, local ownership, sustainable use of resources, adaptation to community goals, carrying capacity, supervision—and evaluation, accountability, training, and promotion. Efforts required include fostering commitment, collaboration, synergy, innovation, continuous evaluation by various stakeholders, and tourism policies that cannot be separated from the tourism pentahelix consisting of government, community, academics, community, business world, and media. Also provides opportunities for tourist villages to form tourism awareness groups (Pokdarwis), provide training in sustainable tourism, hotel management, improve business skills, vocational and professional skills, pay attention to local communities in tourist areas to get jobs, preserve local wisdom and culture, collaborate in cultural tourism, improving tourism services, improving tourism infrastructure, promoting tourism, and implementing other tourism support, all within a short, medium, and long term framework.